2021
DOI: 10.1177/1362168821992264
|View full text |Cite
|
Sign up to set email alerts
|

‘Should textbook images be merely decorative?’: Cultural representations in the Iranian EFL national textbook from the semiotic approach perspective

Abstract: Studies examining culture representation in language textbooks have rarely adopted the semiotic approach, despite its potential for presenting and (re)creating cultural meanings at their various levels (i.e. cultural, intercultural, multicultural, and transcultural) in the co-instantiations of texts, tasks, and images. To address this issue, a qualitative analysis, embarking on the Peircean semiotic theory, was applied on the text-image-task semiotic relationship. It explored its potential for constructing and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 61 publications
1
21
0
Order By: Relevance
“…Investigating these resources in the Indian ELT context could provide avenues for further research. While this research has provided a broad-brush quantitative overview of cultural content, a deeper semiotic analysis of Indian ELT textbooks that investigates the images in these textbooks and their cultural appropriateness related to the text is warranted and should be actively pursued by Indian or South Asian ELT textbook researchers (Derakhshan, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Investigating these resources in the Indian ELT context could provide avenues for further research. While this research has provided a broad-brush quantitative overview of cultural content, a deeper semiotic analysis of Indian ELT textbooks that investigates the images in these textbooks and their cultural appropriateness related to the text is warranted and should be actively pursued by Indian or South Asian ELT textbook researchers (Derakhshan, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Baker (2011) and Nault (2006) argued that the teaching of culture, through ELT textbooks, should be integral to four critical functions (listening, speaking, reading, and writing) of ELT. For this reason, researchers have often engaged with cultural representations in English language teaching textbooks (Davidson & Liu, 2020; Derakhshan, 2021; Thumvichit, 2018; Weninger & Kiss, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…They have concluded that textbooks containing both aesthetic elements and functional purposes can make teaching more attractive (Kiss & Weninger, 2017;Mofidi & Hashemi, 2019;Shen & Su, 2015). This, in turn, can lead to a better learning experience and the promotion of students" learning motivation and aesthetic experiences (Chan et al, 2012;Derakhshan, 2021).…”
Section: Introductionmentioning
confidence: 99%